The Main Character’s Identity through the Narrative Structure in Saltburn (2023) - Zahwa Bilbina Putri Baheransyah; Bunyamin Faisal Syarifudin; Agry Pramita (Journal of English Language and Education, 2026)
Film narratives construct character identity by strategically controlling perspective and information. While previous studies on Saltburn (2023) focus on social class or psychology, this research examines the structural mechanics of identity concealment. By integrating Gérard Genette’s focalization and David Bordwell’s information distribution, this study analyzes how Oliver Quick’s identity is constructed across the Three-Act Structure. Findings show that identity is initially established as marginalized through internal focalization and restricted narration. It is then deconstructed into an ambiguous entity through external focalization and supressed information, and finally revealed as a dominant criminal agent through zero focalization and unrestricted access. The study contributes to narratology by demonstrating how classical theories effectively decode identity engineering in complex contemporary films. Ultimately, it proves that character identity is a product of "who sees" and "who knows," which dictates audience perception